The State of Pediatric Kidney Transplantation in India: A Survey-based Analysis of Practices, Challenges, and Educational Needs - Arka Banerjee; Adwait S. Bendre; Gayatri Munghate; Minnie Bodhanwala (Journal of Indian Association of Pediatric Surgeons)
Background: Technical and immunological advancements have improved patient and graft survival rates in pediatric kidney transplantation (PKT). However, the landscape of PKT in India remains underexplored. We conducted a questionnaire-based survey among Indian pediatric surgeons to delineate contemporary trends in PKT. Methods: The online survey comprised 10 questions assessing pediatric surgeons’ involvement in PKT, existing challenges, and educational needs. Results: Of 610 surveyed pediatric surgeons, 120 responded (19.67% response rate). Majority of the respondents were affiliated with teaching programs, either in the public sector (61.18%) or in corporate setups (25.21%). While 65.83% of respondents managed pediatric patients with chronic kidney disease, only 10% had PKT programs at their institutes. Most of the respondents (67.5%) believed that pediatric surgeons should perform PKTs. Despite this, only 15.83% were part of the renal transplantation team at their institute and only 2.5% routinely performed PKTs. Most of the respondents (63.33%) advocated for mandatory KT exposure during postdoctoral training. Conclusion: Despite enthusiasm among pediatric surgeons, actual involvement remains low. Dedicated PKT programs are necessary to address these challenges along with improved training by integrating transplantation sciences into the pediatric surgical curriculum. The study underscores the need for pediatric surgeons to specialize in transplantation and advocates for policy changes to address the prevailing challenges.